Detection, ultrastucture and phylogeny of Sclerorhabditis neotropicalis (Nematoda: Rhabditidae) nematodes associated with the Azteca ant-Cecropia tree symbiosis - Morera, Jessica (2018)
The nematode involved in ant-plant symbioses have been poorly studied, and originated an area of research that is now receiving increasing attention. One example is Sclerorhabditis neotropicalis that inhabit the nests of Azteca ants in Cecropia trees. The goal of the present study is to increase our knowledge about these organisms and their possible symbiotic relationship with the ants and their host plant. The samples were collected during 2011-2013 in different locations in Costa Rica: Parque Nacional Carara (Puntarenas province), San Pedro de Montes de Oca and Highway 27 (San Jose) and La Selva Biological Station (Sarapiquí, Heredia). We examined 576 internodes from 23 plants, comprising four species of Cecropia (including one non-myrmecophyte) and five Azteca species. S. neotropicalis was found in all but one of the Azteca/Cecropia combinations examined. Queen and worker ants were placed in water in order to dislodge nematodes and the results were largely positive, suggesting that alate queen carry S. neotropicalis between trees and that workers carry them between internodes. In addition to transport, preliminary observations suggest that the ants provide masses of scraped parenchyma (possibly fertilized with feces) as a substrate for bacteria upon which the nematodes presumably feed. We also found S. neotropicalis associated with Azteca in another myrmecophyte, Cordia alliodora, suggesting that this ant/nematode association is not restricted to Cecropia. SEM photographs of S. neotropicalis were provided to supplement the original description of this species, and molecular phylogenetic analyses employing three different markers suggest that Sclerorhabditis forms a well-supported clade of bacteria-feeding nematodes associated with Azteca. Indirect evidence suggests that this is a mutualistic association, but the benefits to the ants remain unknown.